(untitled) (TEL Tempo, Espaço e Linguagem, 2022)
ABSTRACT: to develop the text we have based ourselves on two references. The first is the book “América Latina: males de origem” from Bonfim, published in 1905; the second one is the article “Dom Quixote e os moinhos de vento na América Latina”, from Anibal Quijano.